Geopolitical aspects of Ukrainian foreign policy in the years 1991–2013 (Economic and Political Thought, 2016)
The article aims to analyse Ukrainian foreign policy in the period 1991–2013, i.e. since the country became independent and until Euromaidan inMaidan Nezalezhnosti in Kiev and its geopolitical and economic circumstancesin the context of the present conflict between Russia and Ukraine aswell as its relations with the European Union. The conflict not only droveUkraine to economic ruin but also revealed its other weaknesses and destabilisedits political and social system. It had been growing for a long timeand created threat for the security of Ukraine and peace in Europe and theworld. It put an end to the foreign policy of oscillating between Russia andthe European Union, which Ukraine adopted when it became sovereign(1991). The Ukrainian crisis and conflict with Russia also revealed weaknessesand drawbacks of the European operation and the bankruptcy of itseastern policy. The main thesis is a conclusion that, despite the present conflict,because of geopolitical and geo-economic factors, Ukraine and Russiaare in fact condemned to coexistence and the earlier all the parties to theconflict, especially the West, realise that, the easier it will be to finish theconflict, in fact a war, with benefits for all the involved parties. The EuropeanUnion should do everything to help normalise the relations between the twocountries and develop appropriate strategy towards both Russia and Ukraine.It is necessary to promise less to Ukraine and to stop threatening Russiawith new sanctions, and act more efficiently. This requires cooperation ofthe EU with Ukraine and Russia, without which bringing a peaceful end tothe Ukrainian-Russian conflict is impossible. This does not mean, however,that the EU should give in to Russia’s demands or admit Ukraine to theUnion. On the other hand, Russia cannot violate international law and mustagain accept the European status quo and communicate with Ukraine, theEuropean Union and the United States.